Spousal Kidney Donations in Israel: Religious and Psychoanalytic Perspectives - Kariv, Moriya Hoter (Journal of religion and health, 2026)
In the existing literature on living kidney donation, most studies address either individual altruistic donations to strangers or familial and friendship-based donations within established social ties. The phenomenon explored here diverges from both: married couples in which each spouse independently donates a kidney to an unknown recipient. This dual altruistic donation, carried out separately yet within the shared framework of marriage, illuminates the intersection of individual moral agency, relational dynamics, and religious faith. Using a qualitative methodology, in-depth interviews were conducted with nine Israeli Jewish religious-nationalist couples (eighteen participants) who each donated a kidney to a stranger. The findings reveal that the decision to donate was motivated by intertwined personal, relational, and faith-based factors. Individually, participants sought meaning, fulfillment, and alignment with moral and spiritual values; relationally, donation reflected partnership, mutual support, and shared ethical purpose; spiritually, it was grounded in Jewish concepts such as Tikkun Olam ("world repair") and Pikuach Nefesh (saving a life). A psychoanalytic interpretation drawing on Freud, Klein, and Kohut highlights donation as a process of sublimation, reparation, and self-expansion. The couples’ narratives reveal how altruistic giving can function simultaneously as inner healing, relational repair, and social contribution. The study thus offers an integrated understanding of dual altruistic kidney donation as both a spiritual and relational act of repair, expanding the discourse on altruism, marital intimacy, and faith within contemporary Israeli society.